Legal frameworks of guard of environment unhappy ecological to territory (Journal of actual problems of jurisprudence, 2019)
In the real advanced study some questions of the legal adjusting are examined in area of guard of environment ofunhappy ecological territories. During research scientifi c conclusions and analysis of current legislation are done bothnature protection and natural resourse.Key words: guard of environment, ecological safety, unhappy ecological territories.